Fabrication of a novel disposable glucose biosensor using an electrochemically reduced graphene oxide–glucose oxidase biocomposite. Issue 38 (9th September 2016) - Vijayaraj, Kathiresan; Hong, Suck Won; Jin, Sung-Ho; Chang, Seung-Cheol; Park, Deog-Su
Abstract : A disposable glucose biosensor has been fabricated on the surface of a cost-effective pencil graphite electrode (PGE) by an electrochemical method, using glucose oxidase (GOx) and reduced graphene oxide (rGO). Abstract : A disposable glucose biosensor has been fabricated on the surface of a cost-effective pencil graphite electrode (PGE) by an electrochemical method, using glucose oxidase (GOx) and reduced graphene oxide (rGO). Electrochemical pre-treatment of the PGE enables the adsorption of the rGO–GOx biocomposite. The biocomposites of GOx and rGO were simply prepared by the electrochemical potential cycling method. Efficient immobilization of rGO–GOx is confirmed by field emission scanning electron microscopy, attenuated total reflectance-Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy, and cyclic voltammetry measurements. The rGO nanosheets enhance direct electron transfer (DET) between GOx and the electrode surface. Determination of glucose indirectly by O2 reduction was achieved, which showed high sensitivity, selectivity, reproducibility and stability without a redox mediator. The sensor exhibits a linear current response for a wide range of glucose concentrations between 1.0 × 10 −5 and 1.0 × 10 −3 M ( R = 0.998), and a dynamic range up to 10.0 × 10 −3 M with a detection limit of 5.8 μM. The rGO–GOx biosensor showed an excellent anti-interference ability against electroactive species and proved to be useful for the determination of glucose in human serum samples.